Comparative Risk of Atrial Fibrillation Onset in Statin‐Treated Patients Initiating Icosapent Ethyl and Omega‐3 Acid Ethyl Esters: A Retrospective Cohort Study - Jyotirmoy Sarker; Michael Kim; Samantha Patton; Przemysław B. Radwański; Mark A. Munger; Kibum Kim (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Icosapent ethyl (IPE) and omega‐3‐acid ethyl esters (docosahexaenoic acid [DHA]/eicosapentaenoic acid [EPA]) are approved as adjunct therapies to statins for reducing cardiovascular events in at‐risk patients. However, concerns remain regarding a potential link between IPE and atrial fibrillation (AF). We compared the risk of AF onset in patients who initiated IPE versus DHA/EPA as adjuncts to statin therapy. Methods We conducted a retrospective cohort study using the Merative MarketScan Commercial Claims and Medicare Supplemental database in the United States. An active‐comparator, new‐user study design was applied. Adults diagnosed with dyslipidemia and receiving statin therapy who initiated IPE or DHA/EPA between January 2013 and June 2021 were identified. A propensity score–matched cohort was created using baseline demographic characteristics, comorbidities, and medication dispensing records, with exact matching on therapy initiation period. Patients were followed for up to 2 years while they were on IPE or DHA/EPA therapy to identify incident AF. Cumulative incidence was estimated using Kaplan–Meier methods, and risks between groups were compared using Cox proportional hazards analysis. Results The propensity score–matched cohort included 17 635 participants, with a mean age of 55 years, and was predominantly men (65.4%). Over 2 years, the cumulative incidence of AF from IPE and DHA/EPA was 5.20% (95% CI, 4.62%–5.84%) and 4.07% (95% CI, 3.58%–4.62%) respectively, resulting in a hazard ratio of 1.21 (95% CI, 1.03–1.42). Conclusions These findings suggest that, in adult patients who are AF naïve, IPE may be associated with a higher risk of AF compared with DHA/EPA when used as add‐on therapy with statins.